SISTEM KOMPUTERISASI PENGELOLAAN TUGAS AKHIR MAHASISWA MENGGUNAKAN KONSEP MODEL VIEW CONTROLLER PADA STMIK KHARISMA MAKASSAR - Henry Liputra; Junaedy; Abdul Munir (JTRISTE, 2017)
This research aims to build a computerized Management system of college student thesis by using Model View Controller concept at STMIK KHARISMA Makassar. For that aims, it is proposed to use CodeIgniter Framework, where framework Codeigniter use MVC (Model,View,Controller) method to separates between Model (data logic) from View (presentation logic) and Controller (process logic) so that the application development using MVC concept can be more structured. Based on research result, the author has managed to build a software application of college student thesis Management by using MVC concept inSTMIK Kharisma Makassar. This Application can be used by Prodi and final exam committee to manage STMIK Kharisma Makassar college student thesis and make college student more easy to submit thesis.